2000
DOI: 10.1002/(sici)1097-4628(20000523)76:8<1217::aid-app2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Polyperoxide surfactants for interface modification and compatibilization of polymer colloidal systems. I. Synthesis and properties of polyperoxide surfactants

Abstract: Anhydride-containing polyperoxides were synthesized by copolymerization of 5ϪtertϪbutylperoxyϪ5ϪmethylϪ1ϪhexenϪ3Ϫyne with either maleic anhydride or its blends with styrene. The integral composition of the polyperoxides was theoretically calculated as the copolymerization process proceeded and its direct experimental evidence was obtained. In macrochain-formation behavior, the process was found to be consistent with the generally accepted regularities of binary and ternary copolymerization. By employing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…Polymeric peroxide surfactants PM–MA and PM–MA–S were synthesized by the method described earlier,27 and the characteristics of the products used are presented in Table I. The monomers used—butyl acrylate (BA) and S—were industrial products and were conventionally purified before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric peroxide surfactants PM–MA and PM–MA–S were synthesized by the method described earlier,27 and the characteristics of the products used are presented in Table I. The monomers used—butyl acrylate (BA) and S—were industrial products and were conventionally purified before use.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous article,27 we reported on the synthesis and notable properties of polymer surfactants with peroxide and anhydride functionalities, which are obtained through the radical copolymerization of the peroxide monomer 5− tert‐ butylperoxy−5−methyl−1−hexen−3−yne (PM) with maleic anhydride (MA) or their copolymerization with styrene (S). Their structures are shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…That means that at least a part of peroxide groups was lost in the process of the coating crosslinking, while peroxide functionality was necessary for initiation of graft polymerization of monomers to form grafted polymer films intended for synthesis CdS nanocrystals in situ. But the calculations based on the results of our previous investigations [37,44] revealed that after 120 min heating at 393 K the PM-MA macroinitiator deposited on the slide surface contained nearly a half of initial amount of peroxide groups not decomposed (See Supporting information). Some evidences for that were found in IR-spectrum of coating cured on KBr plate under similar conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PM-MA was synthesized via radical copolymerization of the aforementioned monomers in ethyl acetate at 333 K in the presence of AIBN as initiator as described elsewhere [37]. Polymerization process was carried out till approximately 90 % monomer conversion.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the increasing number of studies on starch blends, there is a lack of publications which explore blends containing large fractions of starch, which is sustainably desirable as a biodegradable renewable blend component. The drawback however is that uncompatibilized blends might suffer from poor adhesion at the interface which leads to poor mechanical properties [2,3,38] .…”
Section: Resultsmentioning
confidence: 99%